2021
DOI: 10.3892/mmr.2021.12338
|View full text |Cite
|
Sign up to set email alerts
|

circCD151 promotes GLI2 expression by regulating miR‑30d‑5p and enhancing proliferation, invasion and stemness of lung cancer

Abstract: To investigate the changes of circular (circ)rna circcd151 expression in lung cancer tissues and cells and its effects on proliferation, migration and invasion of lung cancer cells. The relative expression levels of circcd151 in lung cancer tissues and lung cancer cells (a549 and nci-H292) were determined by reverse transcription-quantitative Pcr. The effects of silencing or upregulation of circcd151 on the activity and clonal forming ability of a549 and nci-H292 cells were detected by ccK-8 and cloning format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In lung cancer, miR-30d-5p also had the function of reducing tumor occurrence and development, which depended on the ceRNA regulatory mechanism of circCD151/miR-30d-5p/GLI2 (Zhao et al, 2021). Taken together, researches into miR-30d-5p in tumorigenesis have progressed, while the specific mechanism needs further investigations.…”
Section: Tumorigenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In lung cancer, miR-30d-5p also had the function of reducing tumor occurrence and development, which depended on the ceRNA regulatory mechanism of circCD151/miR-30d-5p/GLI2 (Zhao et al, 2021). Taken together, researches into miR-30d-5p in tumorigenesis have progressed, while the specific mechanism needs further investigations.…”
Section: Tumorigenesismentioning
confidence: 99%
“…By targeting CCNE2, miR-30d-5p was shown to have an anticancer role (Li et al, 2017;Hosseini et al, 2018). More importantly, since the expression level of miR-30d-5p in tumors clearly differed from that in surrounding tissues, the expression of miR-30d-5p in tumor tissue decreased significantly (Zhao et al, 2021). Therefore, it was considered as a possibly important factor connected with the clinical diagnosis and treatment of NSCLC (Zhang et al, 2017;Gao et al, 2018).…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs can also serve as targets of Tspan genes or mRNAs. For instance, CircTspan24 targets miR-30d-5p to upregulate the expression of GLI2(Glioma cancer-related gene homologous protein 2) and promote the malignant proliferation of lung adenocarcinoma and promote the malignant proliferation of lung adenocarcinoma [ 135 ]. Increasing evidence suggests that there is aberrant expression of miR-203 in tumor stem cells, and it has been found that Tspan27 upregulates the expression of miR-203, which in turn regulates the expression of FZD2 [ 136 ].…”
Section: The Role Of the Tspan Protein Family In Cancer Treatmentmentioning
confidence: 99%